Hirarki Kebutuhan Tokoh Khalil dalam Cerpen “As-Sabiyy al-A’raj” karya Taufiq Yusuf ‘Awwād (Kajian Psikologi Humanistik Abraham Maslow) / The Hierarchy of Needs of Khalil in the Short Story "As -S abiyy al-A’raj" by Taufiq Yusuf ’Awwād (Study of Humanistic Psychology of Abraham Maslow) - Mudore, Syarif Bahaudin; Alliana, Heni (Diwan: Jurnal Bahasa dan Sastra Arab, 2020)
هذا البحث يبحث في وفاء الحاجات النفسيّة للشخص الرئيسيّ خليل الأعرج في القصة القصيرة "الصبيّ الأعرج" لتوفيق يوسف عواد. إن جهاد خليل الأعرج في وفاء حاجاته يشير إلى ان فيه محاولة جدّية مستمرة في وفائها. ومن أغراض هذا البحث وصف عملية وفاء الحاجات النفسية للشخص الرئيسي. وهذا البحث هو بحث نوعي بطريقة التحليلة الوصفية باستخدام نظرية نفسية انسانية لأبراهام ماسلو التي تتكون من خمس طوابق ويسمي بنظام متصاعد. ويجد هذ البحث ان الحاجات للشخص الرئيسي خليل الأعرج قد تم وفائه وفاء جيدا في أربع حوائج وهي حاجة فيسيولوجية، والأمان، والحب والإنتماء، والتقدير. ولكن حاجة تحقيق الذات لايتم وفائها ولايصل خليل إليها لأن فيها مقياس لايقدر خليل على وفائها، وهي: بريئ من الأمراض النفسية، يجري في عملية وفاء حاجاته، رفع قيمة الحياة الأبدية (eternal verities)، ويشغّل كل موهبته واستطاعته، وقوته وغير ذلك. الكلمات المفتاحية: الصبيّ الأعرج، وفاء الحاجة، نفسية إنسانية لأبراهام ماسلو Abstract: This paper examines how to fulfill the psychological needs of the main character Khalil in the short story "As-Sabiyy al-A’raj" by Taufiq Yusuf ‘Awwād. The struggle of the main character Khalil in fulfilling his needs shows that there is a strong effort continuously try to fulfill his psychological needs. The purpose of this study is to describe how the main character’s psychological needs are fulfilled. This research is a qualitative research with analytical description method and is described using Abraham Maslow’s humanistic psychological theory which includes five hierarchies of human needs. This study found that in the five hierarchies of needs attached to the main character Khalil, only four have been properly fulfilled, namely physiological needs, security needs, belonging and loving needs, and self-esteem needs. One of the five needs, namely: the need for self-actualization is not able to be fulfilled by the character Khalil because he is not able to meet the four criteria for the fulfillment of self-actualization, namely: free from psychopathology or disease, has undergone fulfillment of needs, is able to uphold the values of "Being" / the principles of eternal life (eternal verities), and have used all talents, abilities, potentials, and others.